PENGARUH INOVASI PRODUK DAN HARGA TERHADAP NIAT BELI MASKER MUSTIKA RATU (STUDI PADA PENGUNJUNG GIANT HYPERMARKET DI SURABAYA) - FEBRIYANA RAMADHANI, YENI (Jurnal Ilmu Manajemen (JIM), 2017)
The emergence of an increase in the number of female population in Indonesia beeing great opportunity for cosmetics companies. It makes competition between them to create new products that become consumer desires. Therefore, Mustika Ratu issued a product innovation that focus on facial skin care. That is face mask which easy to use and cleaned by peeled off. This research is a conclusive research to analyze and discuss the influence of product innovation and price to purchase intention Mustika Ratu’s face mask. The sampling technique used judgmental sampling technique with the sample number 220 respondents were visitors of Giant Hypermarket in Surabaya between 18 till 30 years old. They had used but had never bought a Mustika Ratu’s face mask. The results of this research showed that there is a significant influence product innovation on purchase intention and price variable influence significant to purchase intention of Mustika Ratu’s face mask. Keywords: product innovation, price, purchase intention